Analytic Method on Characteristic Parameters of Bacteria in Water by Multiwavelength Transmission Spectroscopy. (27th December 2017) - Hu, Yuxia; Zhao, Nanjing; Gan, Tingting; Duan, Jingbo; Yu, Hui Juan; Meng, Deshuo; Liu, Jianguo; Liu, Wenqing
Abstract : An analytic method together with the Mie scattering theory and Beer-Lambert law is proposed for the characteristic parameter determination of bacterial cells ( Escherichia coli 10389) from multiwavelength transmission spectroscopy measurements. We calculate the structural parameters of E. coli cells, and compared with the microscopy, the relative error of cell volume is 7.90%, the cell number is compared with those obtained by plate counting, the relative error is l.02%, and the nucleic content and protein content of single E. coli cells are consistent with the data reported elsewhere. The proposed method can obtain characteristic parameters of bacteria as an excellent candidate for the rapid detection and identification of bacteria in the water.